Effect of donor age on the susceptibility of erythrocytes and erythrocyte membranes to cumene hydroperoxide-induced oxidative stress - (:unkn) unknown (ELSEVIER SCI IRELAND LTD, 1997)
A comparative study on erythrocytes and erythrocyte membranes of healthy elderly and young adults was carried out to understand how the antioxidant defense capacity is effected by aging. The levels of endogenous malondialdehyde and Ca2+-ATPase activity were taken as indices of oxidative damage. In addition, chemiluminescence measurements were performed on intact erythrocytes. The susceptibility of these parameters to in vitro cumene hydroperoxide, under low oxidant level that does not induce hemolysis, was also taken as an age-related indicator of the endogenous peroxidative potential of the erythrocytes. Our data showed that the content of malondialdehyde and Ca2+-ATPase activity did not change with age. Furthermore, the susceptibility of intact erythrocytes to oxidative stress did not change in the elderly group. However, under the same conditions erythrocyte membranes were more susceptible to oxidative damage in the elderly than young adults. Our results also showed that antioxidant defenses were overwhelmed in intact erythrocytes of the elderly at high concentrations of cumene hydroperoxide. (C) 1997 Elsevier Science Ireland Ltd.
Keywords: aging; erythrocyte; oxidative damage; malondialdehyde; Ca2+-ATPase; chemiluminescence; LIPID-PEROXIDATION; CELL; DAMAGE; ENZYMES; INHIBIT; SYSTEM; GHOSTS; BRAIN; RAT